2019
DOI: 10.1111/ijfs.14123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydroxyl radical induced oxidation on water holding capacity and protein structure of jumbo squid (Dosidicus gigas) mantle

Abstract: Summary Protein oxidation is considered as an important issue in food preservation process. In the present study, the potential influence of protein oxidation on water holding capacity and protein structure of jumbo squid (Dosidicus gigas) mantle was investigated. After the hydroxyl radical oxidation, it was found that the carbonyl, surface hydrophobicity and dityrosine content of myofibrillar protein significantly increased (P < 0.05), while the content of total sulphydryl decreased significantly (P < 0.01). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…( p < 0.05). The existing research also showed that as the degree of oxidation increases, the content of dimeric tyrosine increases significantly, which is consistent with the result of this work [ 34 , 35 ]. The results of dimeric tyrosine were consistent with those of the carbonyl group, suggesting that F3 reduces protein oxidation.…”
Section: Resultssupporting
confidence: 92%
“…( p < 0.05). The existing research also showed that as the degree of oxidation increases, the content of dimeric tyrosine increases significantly, which is consistent with the result of this work [ 34 , 35 ]. The results of dimeric tyrosine were consistent with those of the carbonyl group, suggesting that F3 reduces protein oxidation.…”
Section: Resultssupporting
confidence: 92%
“…Alteration in surface hydrophobicity (S 0 ) characterizes the conformational modifications in the protein structure [ 38 ]. The changes in the surface hydrophobicity (S 0 ) of MP treated with different concentrations of OVA-KC are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This was because Trp and Tyr residues were exposed to the polar environment when MP were attacked by •OH. The study by Zhu et al (2019) also illustrated that •OH caused a reduction in the fluorescence intensity of squid MP [34]. The change of the protein conformation caused by oxidation was thought to be the main factor leading to the loss of Tyr fluorescence [24].…”
Section: Tryptophan Fluorescencementioning
confidence: 97%